Submerged impingement cooling for the high thermal flux electric board - Tan, Jun Kai (Nanyang Technological University, 2022)
To meet the demand for rapid heat removal for high-powered electronic devices, submerged impingement cooling has been shown to be a viable way for the removal of high heat flux. The present study will investigate the effects of varying jet outflow nozzle hole count, volumetric flow rate along with different dielectric fluid in a closed-looped system. The jet nozzle hole count for this experiment varies between single, three, four and five holes. The volumetric flow rate that impinges on the 5×5cm ceramic plate ranges from 0.1, 0.2, 0.25 and 0.3 LPM per hole of the jet outflow nozzle. Submerged impingement can be seen to reduce the overall average surface temperature of the heated plate of interest. Findings have also shown that at high volumetric flow rate and a high jet outflow nozzle count will cause overall average surface temperature to decrease at a slower rate. To add on, upon impingement at high volumetric rates and jet outflow nozzles, the segment situated directly underneath the jet nozzle can be seen to decrease instantaneously by an average of 5℃. it was also ascertained that an increase in volumetric flow rate, will give rise to a much better heat transfer coefficient with the five holes jet outflow nozzle count increase by 33.2 W/m^2 K and 6.4 W/m^2 K for the single jet outflow. Used Novec 649 can also be seen to be inferior to Novec 649. Future works were also proposed to enhance and modify the existing setup to gain a better knowledge of the effects of other variables which include, altering the height of the jet to the heated surface, different nozzle geometries and even a vertical setup.